Penile Crohn's disease: a case report. Issue 1 (February 1995) - Neri, I; Bardazzi, F; Fanti, P A; Guidetti, M S
Abstract : Metastatic Crohn's disease is a rare inflammatory condition characterised by cutaneous granulomatous lesions separated from the affected bowel by normal intact skin. Involvement of the genitalia in Crohn's disease is rare and consists of ulcerated lesions in almost all of the cases reported in the literature. We describe a case of penile involvement in a 27 year old man with a 5 year history of Crohn's disease. Should genital involvement precede the bowel disease, patients may consult the sexually transmitted disease service for this problem and the dermatovenereologists may be the first to formulate the diagnosis.